2022
DOI: 10.3390/ijms23073535
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Testosterone in the Elderly: What Do We Know?

Abstract: Testosterone is the most important hormone in male health. Aging is characterized by testosterone deficiency due to decreasing testosterone levels associated with low testicular production, genetic factors, adiposity, and illness. Low testosterone levels in men are associated with sexual dysfunction (low sexual desire, erectile dysfunction), reduced skeletal muscle mass and strength, decreased bone mineral density, increased cardiovascular risk and alterations of the glycometabolic profile. Testosterone replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 177 publications
3
41
2
3
Order By: Relevance
“…The relationship between TT concentrations and ED is well established. The level of hypogonadism that induces ED is disputed and may be influenced by many factors, including extrinsic factors [19,20], patient age, and drug treatment [21]. It has been shown that low TT concentrations are directly related to higher BMI values.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between TT concentrations and ED is well established. The level of hypogonadism that induces ED is disputed and may be influenced by many factors, including extrinsic factors [19,20], patient age, and drug treatment [21]. It has been shown that low TT concentrations are directly related to higher BMI values.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main therapeutic options for the treatment of functional hypogonadism is represented by testosterone replacement therapy (TRT) [ 122 ]. Interestingly, TRT might be an ally in promoting fat mass loss and improving metabolic outcomes through the direct actions of testosterone on AT function [ 10 , 123 ]. Indeed, the exogenous administration of testosterone undecanoate IM 1000 mg every 12 weeks was shown to lead to a significant decrease in body weight (~−15 kg), as well as waist circumference (~−12 cm) [ 124 , 125 ].…”
Section: Effects Of Testosterone Replacement Therapy On Adipose Tissuementioning
confidence: 99%
“…Obesity is also one of the key risk factors for many noncommunicable diseases, such as coronary heart disease, hypertension and stroke, certain types of cancer, type 2 diabetes, gallbladder disease, dyslipidemia, osteoarthritis and gout, and pulmonary diseases, including sleep apnea, and represents one of the principal causes of secondary hypogonadism in men, a condition characterized by the impairment of the hypothalamic–pituitary–testicular (HPT) axis, in which the reduction in testosterone levels is also accompanied by signs and symptoms of hypogonadism, such as decreases in libido, erectile function, semen quality, strength, and mood [ 2 , 3 , 4 , 5 , 6 ]. The prevalence of hypogonadism in normal-weight adult males is around 32%, while about 75% of subjects with severe obesity (BMI > 40 kg/m 2 ) have from hypogonadism [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-lasting hypogonadism rises the risk of physical and mental morbidity [25] , and explains the increased prevalence of depression and energy loss in our PCaSs. This finding, possibly more than sexual dysfunction itself, warrants the consideration of testosterone replacement therapy in long-term tumor-free PCaSs with severe symptoms and low serum testosterone [26] , and supports today’s shorter ADT duration, whenever possible.…”
Section: Discussionmentioning
confidence: 95%